Parametric comparison of different lobe rotor geometry for positive displacement turbine in water distribution network - Baratian, Iman; Ghobadian, Barat; Banakar, Ahmad (Frontiers in Mechanical Engineering, 2023)
The application of hydro turbines for harnessing water energy within distribution networks, as an alternative to pressure relief valves, is steadily increasing. These turbines are particularly suitable for recovering energy from incompressible subsonic fluid flows. In this research paper, three models of positive displacement lobe machine designed to function as water turbines were extensively examined and compared. The three selected turbine types included the circular lobe turbine, the cycloidal arc lobe turbine and the epicycloid arc lobe turbine. These turbines were meticulously designed and developed for their respective applications. Under identical operational conditions, optimization processes were applied to enhance volumetric efficiency and power efficiency for all three turbine variants, each having a different number of blades. A computer program was devised to facilitate the optimization and calculation of blade geometries under various operating conditions. This research delved into the impact of blade geometry type and the number of blades on turbine efficiency and size. The data obtained from the present investigation were systematically analyzed, and the performance of the different turbines were compared. Notably, the circular lobe turbine was found to be the largest among the three, occupying more space. The cycloidal arc requiring a greater amount of material resulting in rotor volume, which subsequently resulted in a higher overall cost. In contrast, the cycloidal arc lobe turbine emerged as the smallest variant, demanding less space for operation. Efficiency-wise, the cycloidal arc lobe turbine exhibited the highest efficiency with two blades, while the circular lobe turbine displayed the lowest efficiency with six blades. Moreover, among the turbines with the same number of lobes, the cycloidal arc lobe turbine consistently demonstrated superior efficiency compared to the circular lobe turbine.